2016
DOI: 10.1002/2016pa002940
|View full text |Cite
|
Sign up to set email alerts
|

Environmental perturbations at the early Eocene ETM2, H2, and I1 events as inferred by Tethyan calcareous plankton (Terche section, northeastern Italy)

Abstract: Several early Eocene hyperthermals have been recently investigated and characterized in terms of temperature anomalies and oceanographic changes. The effects of these climatic perturbations on biotic communities are much less constrained. Here we present new records from the Terche section (northeastern Italy) that, for the first time, integrates data on planktic foraminifera and calcareous nannofossils across three post‐Paleocene‐Eocene Thermal Maximum negative carbon isotope excursions (CIEs). The biomagneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 139 publications
(272 reference statements)
7
24
1
Order By: Relevance
“…The species M. gracilis , M. lensiformis , M. marginodentata , and M. subbotinae were dominant before the J event, and large reductions in the abundance of these four species, which ultimately disappeared within the EECO, give rise to the major morozovellid collapse. The drop in their abundance was not counterbalanced by an increase in Morozovella species that survived into the middle Eocene. Short‐term fluctuations in foraminiferal abundance at Site 1051 closely relate to shifts in bulk carbonate δ 13 C. In general, peaks in Acarinina abundance and lows in Morozovella abundance coincide to early Eocene CIEs and the EECO, similar to what has been observed in several Tethyan successions (e.g., Agnini et al, ; D'Onofrio et al, ; Frontalini et al, ; Luciani et al, , ). We consider that fluctuations in the abundances of Acarinina and Morozovella during CIEs reflect genuine responses of low‐latitude planktic foraminferal populations to early Eocene variations in surface water, although dissolution may enhance the signal.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The species M. gracilis , M. lensiformis , M. marginodentata , and M. subbotinae were dominant before the J event, and large reductions in the abundance of these four species, which ultimately disappeared within the EECO, give rise to the major morozovellid collapse. The drop in their abundance was not counterbalanced by an increase in Morozovella species that survived into the middle Eocene. Short‐term fluctuations in foraminiferal abundance at Site 1051 closely relate to shifts in bulk carbonate δ 13 C. In general, peaks in Acarinina abundance and lows in Morozovella abundance coincide to early Eocene CIEs and the EECO, similar to what has been observed in several Tethyan successions (e.g., Agnini et al, ; D'Onofrio et al, ; Frontalini et al, ; Luciani et al, , ). We consider that fluctuations in the abundances of Acarinina and Morozovella during CIEs reflect genuine responses of low‐latitude planktic foraminferal populations to early Eocene variations in surface water, although dissolution may enhance the signal.…”
Section: Discussionsupporting
confidence: 68%
“…Such dissolution may have partly amplified the foraminiferal assemblage changes (Luciani et al, ). However, at the Tethyan Terche section, D'Onofrio et al (, ) recorded pronounced spikes in Acarinina abundance at the ETM2, H1, and I2 events where planktic foraminferal assemblages are less biased by dissolution. We therefore consider that the increased abundances of Acarinina during the CIEs, and certainly across the major switch following the J event, reflect genuine responses of low‐latitude planktic foraminferal populations to early Eocene variations in surface water properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new late Paleocene to early Eocene Site 1209 benthic isotope record clearly demonstrates the global extent of repeated hyperthermal events during the warmest period of the Cenozoic era, thus providing additional insight into the nature of these events and their relation to orbital and other forcing (Figure ). Multiple carbon isotope excursions are revealed over the course of the Ypresian and Lutetian that correspond in timing and magnitude to hyperthermal events previously observed, for example, in New Zealand, Italy, and the Atlantic realm (e.g., Cramer et al, ; Coccioni et al, ; D'Onofrio et al, ; Galeotti et al, ; Kirtland Turner et al, ; Lauretano et al, , ; Leon‐Rodriguez & Dickens, ; Littler et al, ; Luciani et al, , ; Sexton et al, ; Slotnick et al, , ; Westerhold et al, ; Zachos et al, ). As a consequence of carbonate dissolution, benthic foraminifera are rare in some intervals, and thus, not all hyperthermal layers can be identified by their characteristic paired negative benthic stable carbon and oxygen isotope excursions.…”
Section: Discussionsupporting
confidence: 54%
“…The Late Lutetian Thermal Maximum, aka Chron C19r event, was initially described in late Lutetian bulk isotope data from Demerara Rise (Site 1260; Edgar et al, ) and recently confirmed to be a hyperthermal event (Westerhold et al, ). PETM and ETM2 and other hyperthermals have been documented also in land‐based marine sections, for example, in the Tethyan sections from Italy (e.g., Agnini et al, ; Coccioni et al, ; D'Onofrio et al, ; Galeotti et al, ; Giusberti et al, ; Luciani et al, ). In contrast to the many Atlantic records, multiple hyperthermal events have only been found in Ypresian bulk stable isotope records from New Zealand (e.g., Slotnick et al, ).…”
Section: Introductionmentioning
confidence: 99%